(untitled) (American Journal of Economics and Business Innovation, 2025)
The advent of COVID-19 in CY2020 paved the way for digital financial services (DFS) in the Philippines to prosper and be accepted by many Filipinos. DFS continued to expand up to these days, gradually replacing traditional banking services through innovative technologies. Despite the fast technological advancement and several studies on customer adoption, there is continuous lack of empirical evidence on electronic service quality (E-SERVQUAL) factors that influence clients’ usage of DFS which plays a pivotal role for optimum digitization specifically banks. This study aimed to investigate E-SERVQUAL factors that influence client’s usage of DFS provided by digital banks, traditional banks and electronic money issuers (EMIs). The study employed quantitative and descriptive correlational research design in interpreting the relationship of the variables. Further, the researcher used a self-structured survey questionnaire in gathering primary data from 392 users of DFS. Results showed that efficiency, security and reliability are significant predictors of satisfaction in using DFS. In addition, highly satisfied clients using DFS will likely result to retention of accounts with 57.40% who agreed and 35.70% who strongly agreed. Moreover, there is a need for the government to improve or create new laws that will increase security of DFS. Improving E-SERVQUAL of DFS will increase retention of clients’ usage of DFS. Increasing security through improved or new governmental laws will likely result to increased usage, satisfaction and retention of DFS. The study showed valuable contribution among the limited literature on E-SERVQUAL that influence satisfaction and retention of DFS usage.